Efektivitas rimpang kunyit hitam (curcuma caesia roxb.) terhadap penurunan glukosa darah dan perbaikan ginjal tikus diabetes nefropati - Aini, Zakiyyah Qurrotul; Herdwiani, Wiwin; Wijayanti, Tri (MEDIA ILMU KESEHATAN, 2023)
Background: Diabetes Mellitus is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action or both. Diabetic nephropathy is a degenerative kidney vascular disorder that has a relationship with impaired carbohydrate metabolism or sugar intolerance (Diabetes Mellitus). Black turmeric (Curcuma Caesia Roxb.) is widely used by the community as a traditional medicine and has potential as an antidiabetic.Objective: This study aims to determine the effect of black turmeric extract on decreasing blood glucose levels and its effect on improving kidney histopathology in diabetic nephropathy rats.Method: This research was conducted at the Laboratory of the Center for Food and Nutrition Studies, University of Gajah Mada for the period October-November 2022 consisting of 6 groups. STZ-Na induced rats to obtain a state of hyperglycemia. Examination of blood glucose levels using the GOD-PAP method (enzymatic photometric test).Results: The percentage of blood glucose is decreased levels was 16.75% and repaired kidney histopathology was 6.67% as a score mild damage category (1).Conclusion: Black turmeric rhizome extract (Curcuma Caesia Roxb.) can reduce blood glucose levels and improve kidney function at a dose of 400 mg/kg BW.